1996
DOI: 10.1097/00007890-199612270-00046
|View full text |Cite
|
Sign up to set email alerts
|

Inability of Serum Myocyte Death Markers to Predict Acute Cardiac Allograft Rejection1,2

Abstract: Acute cardiac rejection involves myocyte necrosis. Hence, markers of myocyte death may be useful in diagnosing rejection. Creatine kinase MB, MB isoforms, and troponins I and T were measured in 186 patients undergoing 365 endomyocardial biopsies. No differences were noted with rejection (rejectors vs. nonrejectors: CK=63.8 U/L and 86.6 U/L, P=0.0881; CK MB=2.04 ng/ml and 2.06 ng/ml, P=0.949; troponin T=0.134 ng/ml and 0.0881 ng/ml, P=0.374; troponin I=0.216 ng/ml and 0.707 ng/ml, P=0.357). The time course of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 3 publications
1
27
0
1
Order By: Relevance
“…This is consistent with another study suggesting that elevated cTnT after transplantation is related to donor ischemic time and cardiocyte ischemic injury. 4 Due to the inflammatory response associated with allograft rejection, circulating CRP levels may be expected to be a biomarker for rejection. The present study did not show any significant elevation of CRP levels in samples taken from rejecting patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with another study suggesting that elevated cTnT after transplantation is related to donor ischemic time and cardiocyte ischemic injury. 4 Due to the inflammatory response associated with allograft rejection, circulating CRP levels may be expected to be a biomarker for rejection. The present study did not show any significant elevation of CRP levels in samples taken from rejecting patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that plasma levels of BNP, cTnT, TNF-␣ and IL-6 correlate with the International Society of Heart and Lung Transplantation (ISHLT) rejection grading system for endomyocardial biopsy scores, whereas other studies found no such correlation. [1][2][3][4][5][6] Therefore, no general consensus has been reached regarding the interrelationships of these neurohumors or their relationship to rejection status in cardiac transplant patients.…”
mentioning
confidence: 99%
“…The c-statistic was 0.82 and at the optimized cut point of 15 ng/L sensitivity was 94% and the NPV was 99%, both notably higher than previous reports with standard assays (11%-89% and 79%-96%, respectively). 7,10,11,13,27 …”
Section: Use Of the Hs Assay To Assess Rejectionmentioning
confidence: 99%
“…It is well established that cTnT plasma concentrations are increased during the ¢rst month posttransplantation in response to surgery-related trauma. 6,7 However, contradictory results have been reported with regard to a potential relationship between rejection and plasma concentration of cTnT as a marker of myocardial necrosis. Higher concentrations of cTnT have been found in blood taken from a central line in patients diagnosed with cardiac rejection, 8 providing useful information complementary to the EMB.…”
Section: Introductionmentioning
confidence: 99%